Analysis of Quality of Work Life Effect on Organizational Citizenship Behavior with Work Satisfaction as A Variable Intervening - Sri Rahayu; Harianto Harianto; Megasari Gusandra Saragih (AIBPM Publisher, 2019)
This research analyzes the influence of quality of work life on organizational citizenship behavior with job satisfaction as an intervening variable. This type of quantitative study with Structural Equation Modeling (SEM) analysis tool with AMOS-20 (Analysis of Moment Structure) device. The sample in this study was 105 Regional Secretariat Officer of the Bireuen District government. The results showed that quality of work life has significant effect on job satisfaction and organizational citizenship behavior. Job satisfaction has significant effect on organizational citizenship behavior. Job satisfaction is a partial mediation of the influence between quality of work life on organizational citizenship behavior.